KHUSHANZAMON-NATIONAL ETHNOGRAPHIC FOLKLORE ENSEMBLE (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
It was written a little more seriously, since it was for a scientific article, I looked at the facts.